Vessel Wall Injury and Arterial Thrombosis Induced by a Photochemical Reaction - Saniabadi, Abby R; Umemura, Kazuo; Matsumoto, Nobuteru; Sakuma, Sadayuki; Nakashima, Mitsuyoshi (Thrombosis and Haemostasis, 1995)
Arterial thrombosis may be initiated in an experimental animal by a photochemical reaction between transmural green light and i.v. administered Rose Bengal, a photosensitizer dye. In this study, scanning electron microscopy has been used to reveal the nature of vessel injury and the cellular composition of the photochemically induced thrombus. A 5 mm segment of the guinea pig femoral artery was occluded by a thrombus about 10 min after irradiation with green light in the presence of systemically administered Rose Bengal. Electron microscopy revealed that following photochemical reaction, endothelial cells first contract and, with further irradiation, become detached from the vessel wall, with their cell membrane being destroyed at the irradiated site where an occlusive platelet-rich thrombus was formed. Endothelial cell injury and vessel occlusion could be completely inhibited by the aminothiol, DL-cysteine administered i.v. 1 min after Rose Bengal. The mechanism of endothelial injury in this model appears to be by singlet molecular oxygen, 1O2 formed by energy transfer from the photo-excited dye to O2.